2019
DOI: 10.1111/ivb.12259
|View full text |Cite
|
Sign up to set email alerts
|

Factors linked to interannual variation in the metazoan parasite communities of black skipjack, Euthynnus lineatus (Pisces: Scombridae)

Abstract: Marine parasite communities can exhibit temporal and spatial changes in response to seasonal and local variations in several biotic and abiotic environmental factors. Limited attention has been given to the influence of abiotic factors, so their effects on parasite community structure remain unclear. A total of 496 specimens of Euthynnus lineatus were collected over a 7-year period (2012-2018) from Acapulco Bay, Mexico. Their parasite communities were analyzed to determine if they experience interannual variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Species richness at the component level (13-19 species, table 3) was similar to that reported for other Lutjanus species: L. Lutjanus guttaus (19 species); Lutjanus campechanus (21 species); Lutjanus synagris (25 species); and Lutjanus griseus (20 species) (Argáez-García et al, 2010;Montoya-Mendoza et al, 2014Morales-Serna et al, 2017). However, the overall parasite fauna for L. peru was 25 species even though the highest species richness registered at the component level was 19 parasite species (April 2019, table 3).…”
Section: Component Communitiessupporting
confidence: 78%
See 2 more Smart Citations
“…Species richness at the component level (13-19 species, table 3) was similar to that reported for other Lutjanus species: L. Lutjanus guttaus (19 species); Lutjanus campechanus (21 species); Lutjanus synagris (25 species); and Lutjanus griseus (20 species) (Argáez-García et al, 2010;Montoya-Mendoza et al, 2014Morales-Serna et al, 2017). However, the overall parasite fauna for L. peru was 25 species even though the highest species richness registered at the component level was 19 parasite species (April 2019, table 3).…”
Section: Component Communitiessupporting
confidence: 78%
“…Endoparasites represented 94% of the total individual parasites recovered in this host species. Fish species with carnivorous habits, such as L. peru , tend to be associated with higher parasite species numbers and total endoparasite loads, which they acquire by consuming infected prey (Luque et al , 2004; Miranda-Delgado et al , 2019; Santos-Bustos et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruíz-Pérez, Cerdenares-Ladrón de Guevara, López-Herrera, & Altamirano-Ramírez (2016) indicated that E. lineatus feed mainly on crustaceans in the coast of Oaxaca. Miranda-Delgado et al (2019) found that the E. lineatus trophic spectrum included 14 prey items in the study area, among which were fish, crab, penneid larvae, mollusk larvae, isopods, ostracods, juvenile squid, amphipods, and polychaetes. Artunduaga (1972) reported that S. sierra is a carnivorous fish found at the upper levels of the food chain, whose existence depended mainly on planktivorous fish.…”
Section: Discussionmentioning
confidence: 99%
“…Trophic biology studies show that epipelagic scombrids are widely known as opportunistic and generalist predators, which means that their diet is made up of many organisms from different levels of the food chain (Paxton, 1998;Olson et al, 2016). Internationally, the species of the Scombridae family have mainly been reviewed for systematic, zoogeographical purposes and some parasitological investigations; however, few studies have focused on the interaction between ecological factors and the parasite community of a specific host (Chero et al, 2016;Miranda-Delgado et al, 2019;Santos-Bustos et al, 2020.…”
Section: Introductionmentioning
confidence: 99%